Design & Simulation of Turbo Decoder for BER Calculation (International Journal of Engineering and Computer Science, 2017)
Turbo decoders applied in wireless communications are complex and dissipate large amount of power. In this paper, we investigate design & simulation of Turbo algorithm for wireless communications applications, including our proposed Simulink model of Turbo decoder. The schemes employed in our low-power design are clock-gating and toggle filtering. We described the behavior of Turbo decoders in Matlab Simulink Model and synthesized using a Simulink Communication tool. The analyzing circuits were replaced and routed in the standard cell design environment. BER estimation obtained through different simulations indicates that the proposed design reduces the BER of an original Turbo decoder design by 55%.